PENGARUH KARAKTERISTIK INDIVIDU, BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR PELAYANAN PAJAK PRATAMA LUBUK PAKAM - Wendra Fatawa (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2020)
The formulation of the problem in this research is how the influence of individual characteristic on employees  performance. How  influence of work environment on employees  performance. How  influence of  work of load on employees  performance. How  influence of  individual characteristic, work environment and  work of load on employees  performance. The purpose of this research is for know influence and analize of  individual characteristic on employees  performance. For know influence and analize of work environment on employees  performance. For know influence and analize  work of load on employees  performance. For know influence and analize individual characteristic, work environment and  work of load on employees  performance.  The sample in this research is 86 employees, with data analysis technique used is multiple linear regression analyze.The results of this research explain that individual characteristic effect has a positive and significant on employee  performance. Work environment effect has a positive and significant on employee  performance.  Work of load effect has a positive and don’t significant on employee  performance. Individual characteristic, work environment and  work of load effect  have a positive and significant on employee  performance